Faktor-Faktor yang Mempengaruhi Financial Management Behavior - Raden Arvi Arsytania; Sri Zaniarti (MBIA, 2023)
This study aims to examine and analyze the influence of factors such as financial knowledge, locus of control and income on financial management behavior in students of the Management Study Program, Maranatha Christian University. The number of samples in this study amounted to 240 respondents and the sampling technique was probability sampling with simple random sampling technique. The data was processed and analyzed using multiple linear regression. The obtained result showed that financial knowledge has an effect on financial management behavior, while locus of control and income have no effect on financial management behavior. Keywords: financial management behavior, financial knowledge, income, locus of control. Abstrak Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh faktor-faktor seperti financial knowledge, locus of control dan income terhadap financial management behavior pada mahasiswa Program Studi Manajemen Universitas Kristen Maranatha. Jumlah sampel dalam penelitian ini berjumlah 240 responden dan teknik pengambilan sampel dengan probability sampling dengan Teknik simple random sampling. Data diolah dan dilakukan analisis menggunakan regresi linear berganda. Didapatkan hasil yaitu financial knowledge berpengaruh terhadap financial management behavior sedangkan locus of control serta income tidak berpengaruh terhadap financial management behavior. Kata kunci: financial management behavior, financial knowledge, income, locus of control.